A Critical Review on the Status and Progress of Microalgae Cultivation in Outdoor Photobioreactors Conducted over 35 Years (1986–2021) - Nilay Kumar Sarker; Prasad Kaparaju (Energies, 2023)
Microalgae, a renewable bio-resource, are considered a potential value-added commodity and a tool to combat climate change. Microalgal research has received worldwide attention recently. Different perspectives have been explored, but cultivation in outdoor photobioreactors (PBRs) is still a less explored field. This review summarizes the studies conducted on the microalgae cultivated in outdoor PBRs only. The locations, algal strains, PBRs, and cultivation media used in these studies were identified and tabulated. Different aspects of outdoor algal cultivation in PBRs, such as temperature control, light intensity control, photosynthetic efficiency (PE), the outdoor adaptation of strains, PBR designs, and algal growth and biochemical composition variation from the weather, were studied and reviewed. A brief review of downstream processes and environmental and economic impacts was also conducted. This review summarizes what has been carried out in this field so far and will help researchers to determine what further work needs to be conducted and in which direction to proceed.